Hepatitis D infection induces IFN-β-mediated NK cell activation and TRAIL-dependent cytotoxicity - Groth, Christopher; Maric, Jovana; Garcés Lázaro, Irene; Hofman, Tomáš; Zhang, Zhenfeng; Ni, Yi; Keller, Franziska; Seufert, Isabelle; Hofmann, Maike; Neumann-Haefelin, Christoph; Sticht, Carsten; Rippe, Karsten; et al. (Frontiers in Immunology, 2023)
Background & Aims The co-infection of hepatitis B (HBV) patients with the hepatitis D virus (HDV) causes the most severe form of viral hepatitis and thus drastically worsens the course of the disease. Therapy options for HBV/HDV patients are still limited. Here, we investigated the potential of natural killer (NK) cells that are crucial drivers of the innate immune response against viruses to target HDV-infected hepatocytes. Methods We established in vitro co-culture models using HDV-infected hepatoma cell lines and human peripheral blood NK cells. We determined NK cell activation by flow cytometry, transcriptome analysis, bead-based cytokine immunoassays, and NK cell-mediated effects on T cells by flow cytometry. We validated the mechanisms using CRISPR/Cas9-mediated gene deletions. Moreover, we assessed the frequencies and phenotype of NK cells in peripheral blood of HBV and HDV superinfected patients. Results Upon co-culture with HDV-infected hepatic cell lines, NK cells upregulated activation markers, interferon-stimulated genes (ISGs) including the death receptor ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), produced interferon (IFN)-gamma and eliminated HDV-infected cells via the TRAIL-TRAIL-R2 axis. We identified IFN-beta released by HDV-infected cells as an important enhancer of NK cell activity. In line with our in vitro data, we observed activation of peripheral blood NK cells from HBV/HDV co-infected, but not HBV mono-infected patients. Conclusions Our data demonstrate NK cell activation in HDV infection and their potential to eliminate HDV-infected hepatoma cells via the TRAIL/TRAIL-R2 axis which implies a high relevance of NK cells for the design of novel anti-viral therapies.